Using One-hop and Two-hop Neighbouring Information to Defend Against Sybil Attacks in Stationary Wireless Sensor Network - Elham Bahmani; Sheida Dashtevan; Abdusalam Shaltooki; Mojtaba Jamshidi (JOIV : International Journal on Informatics Visualization, 2019)
Considering the application of wireless sensor networks (WSNs) in critical areas like war fields, establishing security in these networks is of great challenge. One of the important and dangerous attacks in these networks is the Sybil attack. In this attack, a malicious node broadcasts several IDs simultaneously. Thus, the malicious node of the adversary attracts high traffic to itself and disrupts routing protocols and affects other operations of the network like data aggregation, voting, and resource allocation, negatively. In this paper, an efficient algorithm based on one-hop and two-hop neighborhood information is proposed to detect Sybil nodes in the stationary WSNs. The proposed algorithm is executed locally with the collaboration of neighboring nodes. The main purpose of the proposed algorithm is to increase the accuracy of detecting Sybil nodes under various conditions including the condition in which a malicious node broadcasts a few numbers of Sybil IDs which is the shortcoming of most existing algorithms. The proposed algorithm is simulated in MATLAB and its efficiency is compared with two similar algorithms in terms of true and false detection rates. The proposed algorithm not only reduces communication overhead but also increases the accuracy of detecting Sybil nodes compared to two similar algorithms.